Role of CD38 in anti-tumor immunity of small cell lung cancer - Taniguchi, Hirokazu; Chavan, Shweta S.; Chow, Andrew; Chan, Joseph M.; Mukae, Hiroshi; Rudin, Charles M.; Sen, Triparna (Frontiers in Immunology, 2024)
Introduction: Immune checkpoint blockade (ICB) with or without chemotherapy has a very modest benefit in patients with small cell lung cancer (SCLC). SCLC tumors are characterized by high tumor mutation burden (TMB) and low PD-L1 expression. Therefore, TMB and PD-L1 do not serve as biomarkers of ICB response in SCLC. CD38, a transmembrane glycoprotein, mediates immunosuppression in non-small cell lung cancer (NSCLC). In this brief report, we highlight the potential role of CD38 as a probable biomarker of immunotherapy response in SCLC.We evaluated the role of CD38 as a determinant of tumor immune microenvironment in SCLC with bulk and single-cell transcriptomic analyses and protein assessments of clinical samples and preclinical models, including CD38 in vivo blockade.In SCLC clinical samples, CD38 levels were significantly correlated with the gene expression of the immunosuppressive markers FOXP3, PD-1 and CTLA-4. CD38 expression was significantly enhanced after chemotherapy and ICB treatment in SCLC preclinical models and clinical samples. A combination of cisplatin/etoposide, ICB, and CD38 blockade delayed tumor growth compared to cisplatin/ etoposide.Our study provides a preliminary but important direction toward exploring CD38 as a potential biomarker of ICB response and CD38 blockade as a combination strategy for chemoimmunotherapy in SCLC.